DETERMINANTS OF INVESTMENT INTEREST AMONG MANAGEMENT STUDENTS, CASE STUDY: STUDENTS OF UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR - Firdaus, Andrew Baihaqi; Wikartika, Ira (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Investment involves the long-term allocation of funds with the objective of generating profits. Notably, the number of investors has experienced a significant increase over the years. This phenomenon can be attributed to several factors that positively influence the growth of future investment users, thereby motivating the investment interest of potential investors to allocate their capital in the Indonesian capital market. This research aims to analyze investment interest by examining the influence of financial literacy, financial self-efficacy, risk perception, and return perception on investment interest among Management students of UPN "Veteran" East Java. The population for this study comprised Management students from the 2020 to 2023 batches at UPN "Veteran" East Java. The sampling technique employed was stratified random sampling, with 100 respondents selected as the sample. Data collection was carried out through a questionnaire method, and the data analysis technique utilized was PLS. The findings of the study indicate that financial self-efficacy, return perception, and risk perception significantly influenced investment interest, while financial literacy did not have a significant effect on student investment interest.